Pembagian Harta Tak Bergerak Akibat Perceraian Berdasarkan Putusan Nomor 149/Pdt.G/2017/Pn Tabanan - Agung Istri Altia Dwi Widaswari; I Nyoman Putu Budiartha; I Made Minggu Widyantara (Jurnal Konstruksi Hukum, 2022)
The law of husband and wife wealth due to divorce is joint property and must be divided by 50% for husband and wife. Equitable distribution of shared assets, a dispute will arise between the two. If the joint property is in the form of immovable objects, the parties maintain their share rights without anyone intending to relinquish their rights to be sold to other parties, then how to resolve it. The formulation of the problem is 1. How is the distribution of property in the form of immovable objects after divorce without a marriage agreement? 2. What is the judge's consideration in the distribution of immovable property after divorce without a marriage agreement? The research method used is normative legal research. The results of the discussion of the distribution of assets after divorce in the absence of a marriage agreement can be carried out by mediation or through the court. Regarding the distribution of assets in decision Number 149/Pdt.G/2017, it is following the evidence, facts in court. The author suggests judges be more careful in deciding cases. The legislature must continue to revise the law in order to keep up with the development of society.